It takes two to tango: Knowledge transfer between expatriates and host country nationals - Hsu, Yu‐Shan; Chen, Yu‐Ping; Chiang, Flora F. T.; Shaffer, Margaret A. (Human Resource Management, 2022)
AbstractIntegrating conservation of resource (COR) theory and the theory of relational organizing, we conceptualize expatriate–host country national (HCN) knowledge transfer as resource gains between the sender and receiver. Based on a sample of 107 expatriate–HCN dyads, we found that when the knowledge receiver, be it an expatriate or HCN, is high on cultural intelligence (CQ), the sender will be more likely to perceive higher levels of trust in the receiver and shared vision with the receiver. These cognitive responses to the receiver's CQ are instrumental in facilitating the receiver's knowledge acquisition. We also identified the sender's perceptions of the collaborative‐based HR configuration as a contextual condition that strengthens the relationship between the knowledge receiver's CQ and the sender's perceived trust in the receiver and shared vision with the receiver.